PENDIDIKAN KARAKTER DALAM PEMBELAJARAN IPS DI SMP NEGERI 9 BANJARBARU - Ika Mayasari Candra (JURNAL SOCIUS, 2014)
To support the enforceability of character education, schools should be conditioned as a major supporter of activities especially in SMP Negeri 9 Banjarbaru.  Character education can also be demonstrated in the behavior and attitudes of teachers in providing. Teachers are expected to be the role models for their students.  This study used a qualitative research method, which gives an idea of character education in teaching social science in SMP Negeri 9 Banjarbaru.  Data collection techniques in the study were interviews, observation, and documentation. Based on the results of the study character education in schools is also strongly associated with the management of the school, how the character education is adequately planned, implemented, and evaluated in the educational activities in schools.  Therefoe, the character education should be combaining by many values, such us: religious, honesty, tolerance, discipline, curiosity, achievement appreciation, environmental care, social care, and responsibility.Keywords: character education and social studies learning.